2016
DOI: 10.1126/scitranslmed.aaf4823
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of ileal bile acid uptake protects against nonalcoholic fatty liver disease in high-fat diet–fed mice

Abstract: Non-alcoholic fatty liver disease (NAFLD) is the most common chronic liver disease in the Western world, and safe and effective therapies are needed. Bile acids (BAs) and their receptors (including the nuclear receptor for BAs, FXR) play integral roles in regulating whole body metabolism and hepatic lipid homeostasis. We hypothesized that interruption of the enterohepatic BA circulation using a luminally-restricted Apical Sodium-dependent BA Transporter (ASBT) inhibitor (ASBTi; SC-435) would modify signaling i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
170
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 181 publications
(184 citation statements)
references
References 53 publications
14
170
0
Order By: Relevance
“…Due to the metabolic interactions between the intestinal bile acid pool and the gut microbiota, the administration of bile acid-binding resins might readily alter the composition of intestinal microbial species, and might also have therapeutic value in the treatment of gastrointestinal cancers, particularly HCC. In addition, inhibition of enterohepatic circulation using ASBT inhibitor SC-435 improved both hepatic and systemic symptoms of nonalcoholic fatty liver disease (NAFLD) in mice fed a HFD 198 . Another ASBT inhibitor, A4250, ameliorated liver cholestasis and bile duct injury in a mouse model of PSC 199 .…”
Section: Targeting Bile Acid Signallingmentioning
confidence: 99%
“…Due to the metabolic interactions between the intestinal bile acid pool and the gut microbiota, the administration of bile acid-binding resins might readily alter the composition of intestinal microbial species, and might also have therapeutic value in the treatment of gastrointestinal cancers, particularly HCC. In addition, inhibition of enterohepatic circulation using ASBT inhibitor SC-435 improved both hepatic and systemic symptoms of nonalcoholic fatty liver disease (NAFLD) in mice fed a HFD 198 . Another ASBT inhibitor, A4250, ameliorated liver cholestasis and bile duct injury in a mouse model of PSC 199 .…”
Section: Targeting Bile Acid Signallingmentioning
confidence: 99%
“…Administration of an ASBT inhibitor in mice fed a HFD led to increased clearance of BAs in feces, increased hepatic BA synthesis, decreased FGF15, increased I-BABP, and decreased hepatic steatosis (Rao et al, 2016). Furthermore, the hepatic BA pool shifted towards FXR agonistic BAs and SREBP1c expression decreased, but the hepatic steatosis score was not significantly improved in diet-induced obese mice given a short course of an ASBT inhibitor (Rao et al, 2016). Another study using a different ASBT inhibitor, 264W94, demonstrated improved glucose tolerance and upregulation of hepatic FXR in Zucker Diabetic Fatty rats (Chen et al, 2012).…”
Section: Current Therapiesmentioning
confidence: 99%
“…Inhibition of the IBAT (ASBT) led to increased fecal bile acid loss and altered the bile acid pool to increase bile acids, which are agonists to FXR and enhance resistance to high fat diet-induced hepatic steatosis and glucose intolerance (40). Conversely, fexaramine, an intestinal FXR agonist, also ameliorated high fat diet-induced weight gain, insulin resistance and hepatic steatosis (41).…”
Section: Pharmacotherapeutics Of Bile Acids and Receptorsmentioning
confidence: 99%